A Christianity worth believing Hope-filled, open-armed, alive-and-well faith for the left out, left behind, and let down in us all - Pagitt, Doug (San Francisco Jossey-Bass Publishers, 2008)
A new hope-filled, untamed vision of Christian faith, life, and meaning Explores new ways to think about Christianity, with new hopes, new understandings, and new outcomes so that they may also discover the renewal that comes with an expanded vision of li
Keywords: Christianity -- 21st century. Christian life. Postmodernism -- Religious aspects -- Christianity